1971
DOI: 10.1210/jcem-32-5-604
|View full text |Cite
|
Sign up to set email alerts
|

Familial Male Pseudohermaphroditism with Gynecomastia Due to a Testicular 17-Ketosteroid Reductase Defect. I. Studiesin Vivo

Abstract: A patient with familial male pseudohermaphroditism was considered to be a normal female up to the time of puberty. At puberty, she had normal breast development but there was simultaneous enlargement of the clitoris and the body hair developed with a male distribution. The internal genitalia were male in type. Under basal conditions, the plasma concentration of testosterone (T) was low for a male subject but plasma levels of dehydroepiandrosterone (DHA) and dehydroepiandrosterone sulfate (DHAS) were 2-3 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
2
1

Year Published

1974
1974
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(66 citation statements)
references
References 21 publications
9
52
2
1
Order By: Relevance
“…In some cases, this virilization leads to the spontaneous adoption of a male gender role (1,(3)(4)(5)(6). The presence of these features is thought to be the result of other isoenzymes of 17beta-HSD in extragonadal tissues that may not be affected by the genetic defect and are capable of converting A to T. The theory of extragonadal enzymatic activity is supported by recent work by Andersson et al who found negligible amounts of testosterone (~5%) in spermatic venous blood of these patients (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, this virilization leads to the spontaneous adoption of a male gender role (1,(3)(4)(5)(6). The presence of these features is thought to be the result of other isoenzymes of 17beta-HSD in extragonadal tissues that may not be affected by the genetic defect and are capable of converting A to T. The theory of extragonadal enzymatic activity is supported by recent work by Andersson et al who found negligible amounts of testosterone (~5%) in spermatic venous blood of these patients (7).…”
Section: Discussionmentioning
confidence: 99%
“…Defective testosterone synthesis can be due to a mutation in any of the five enzymes involved in the conversion of cholesterol to testosterone (2). 17beta hydroxysteroid dehydrogenase 3 (17beta-HSD3) deficiency, also known as 17-ketosteroid reductase deficiency, is a rare autosomal recessive cause of male pseudohermaphroditism resulting from a defect in the final reversible step in testosterone synthesis in the testes, specifically, the conversion of androstenedione to testosterone (3,4). This enzymatic defect results in elevated levels of blood androstenedione (A) and either low or normal male levels of testosterone (T), usually reported as an increased plasma androstenedione-to-testosterone ratio (A/T) (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSD is defined as a congenital condition in which development of chromosomal, gonadal or anatomical sex is atypical in such individuals (Hughes et al, 2006). 46, XY DSD is an autosomal recessive form of DSD which was first described in 1971 (Saez et al, 1971). Disturbances of androgen production can occur in all steps of T biosynthesis and its conversion into DHT.…”
Section: β-Hsd and 17β-hsd Deficiencymentioning
confidence: 99%
“…17 -hydroxysteroid dehydrogenase type 3 (17 -HSD3) deficiency (OMIM #264300), originally described as 17-ketosteroid reductase deficiency (Saez et al, 1971), is an autosomal recessive disorder which represents the most common defect of the biosynthesis of T in 46,XY DSD (Bertelloni et al, 2004;Mendonca et al, 2000). This disorder is due to an impaired conversion of Δ4-A into T in the testes (Bertelloni et al, 2009;Faienza et al, 2008).…”
Section: β-Hydroxysteroid Dehydrogenase Type 3 Deficiencymentioning
confidence: 99%